Is interactive ozone chemistry important to represent polar cap stratospheric temperature variability in Earth-System Models? - Harald E Rieder; Gabriel Chiodo; Johannes Fritzer; Clemens Wienerroither; Lorenzo M Polvani (Environmental Research Letters, 2019)
Considering the representation of the atmosphere, the current generation of Earth-System Models (ESMs) differs mainly in the representation of the stratospheric ozone layer and its variability and changes. So-called high-top models have a well resolved stratosphere and typically calculate ozone chemistry interactively, low-top models on the other hand rely on parameterized ozone chemistry or prescribed climatological ozone fields and have a model top below the stratopause. Here we investigate whether interactive ozone chemistry is important for representing temperature variability and extremes in the Arctic polar stratosphere. To this end we analyze a suite of two 200 year sensitivity simulations, one with interactive ozone chemistry and one without, performed with the Whole Atmosphere Community Climate Model version 4 (WACCM4), a stratosphere-resolving version of the National Center for Atmospheric Research Community Earth-System Model. We find a tight coupling between ozone and temperatures over the Arctic polar cap, manifesting in increased variability in stratospheric spring-time temperatures in simulations with interactive chemistry compared to simulations imposing climatological mean ozone abundances. Our results indicate that stratospheric temperature extremes regularly occurring in simulations with interactive chemistry are absent in uncoupled model simulations.